Role Of Ichtiophaguous Birds In Biocenosis. - Boltayeva Zarina Azamatovna (Zien Journals, 2024)
The article discusses the role of ichthyophages, that is, fish-eating birds, in the biocenosis, and bioecological features. Information is presented on fish-eating birds found in fish farms in the Bukhara region, characteristics of encounters in reservoirs, periods of migration, and nesting ecology of nesting species.
Keywords: ixtiofag; spectrum of food; illness of ink; eye cataract